Understanding perinatality from the perspective of the selection-byconsequences model - Rocha, Carolina Neves da; Linares, Ila Marques Porto; Weiss, Julia Vasconcellos Pacheco (Perspectivas em Análise do Comportamento, 2023)
Perinatal mental health is a research area that investigate the period around the birth of a baby and its implications, especially on the woman who’s becoming a mother. This study aimed to raise functional and contextual variables from the reflections of women, mothers and behavior analysts, about their personal experiences. For this, three women were interviewed, who were behavior analysts, involved in teaching, research and/or supervision, and who had had children from 1 year to 2 years and 2 months before. From their reflections, concepts and behavioral processes involved in perinatality were apprehended, organized into the following categories: antecedent conditions; repertoire/classes of responses; consequences; phylogenetic aspects; interlocking behavioral contingencies and metacontingencies and; emotional collaterals. Data were discussed under the light of the selection by consequences model and articulated with the literature surveyed. The main contribution of the study was to raise several variables that can be better investigated in further studies, as well as being considered in clinical practice in cases involving the transition to parenthood.